Pengaruh Persepsi Profesi Guru, Efikasi Diri, Lingkungan Keluarga, Dan Teman Sebaya Terhadap Minat Menjadi Guru Mahasiswa Prodi Pendidikan Akuntansi UNESA - Tifani, Savira Sarah; Wahjudi, Eko (Jurnal Pendidikan Akuntansi (JPAK), 2022)
A good education is a bridge to make a nation great and advanced. In other words, the teacher has a big role in it all. Teachers have a big role in realizing the success of education. This relates to education students who have been prepared to become teachers in the future. However, not all students set future goals to become teachers. Several causes can influence interest in becoming a teacher, including student perceptions of the teaching profession, student self-efficacy, family environment, and peers. This study aims to determine the effect of perceptions of the teaching profession, self-efficacy, family environment, and peers on students' interest in becoming teachers. This research belongs to the category of quantitative research. The research population used was students of the 2018 Accounting Education Study Program, Surabaya State University as many as 60 students with a sampling technique, namely saturated sampling. The method of data collection is done through a questionnaire. Based on the test results, it is known that 1) The perception of the teaching profession has no significant effect on student interest in becoming a teacher, 2) Self-efficacy has no significant effect on student interest in becoming a teacher, 3) Family environment has a significant effect on student interest in becoming a teacher, 4) Peers have a significant effect on students' interest in becoming teachers, and 5) Perceptions of the teaching profession, self-efficacy, family environment, and peers simultaneously have a significant effect on students' interest in becoming teachers.